Morfologia kryształów - Szurgot, Marian (Wydawnictwo Uniwersytetu Łódzkiego, 2005)
Macromorphology of minerals and synthetic crystals exhibited at the Geological Museum of the University of Łódź has been described. Effects of internal structure and environmental factors such as growth temperature, supersaturation, impurities and gravitational field have been illustrated and explained.
Morphology of crystals
Keywords: morfologia kryształów; kształt kryształu; kryształy dendrytyczne; kryształy bliźniacze; crystal morphology; crystal shape; dendritic crystals; twin crystals